2′-Hydroxycinnamaldehyde induces ROS-mediated apoptosis in cancer cells by targeting PRX1 and PRX2 - Yae Jin Yoon; Yu-Jin Lee; Jiyeon Choi; Seung-Wook Chi; Sangku Lee; Kyung Chan Park; Byoung-Mog Kwon; Dong Cho Han (Results in Chemistry)
2′-Hydroxycinnamaldehyde (HCA) is a component of the commonly used spice cinnamon, which has beneficial effects on cancer, allergies, bacterial/viral infections, and Alzheimer’s disease. Our previous study showed that HCA induced reactive oxygen species (ROS) and apoptosis in cancer cells, and pretreatment of cancer cells with antioxidants abolished HCA-mediated ROS production and apoptosis. This indicates that ROS are critical effector for HCA activity. However, the molecular target of HCA for ROS induction has not been identified. In the present study, we identified peroxiredoxin 1 (PRX1) and peroxiredoxin 2 (PRX2) as target proteins of HCA using affinity chromatography, and further confirmed these association using a cellular thermal shift assay (CETSA). In addition, we used mutagenesis to identify important cysteine residues in PRX1 for HCA binding. PRX1 has four cysteines (Cys52, Cys71, Cys83, and Cys173), and when Cys173 (but not the other cysteine sites) was mutated to serine, it was unable to bind biotin-conjugated HCA, suggesting that Cys173 is important for HCA binding. Treatment of SW620 cancer cells transfected by control vector with 20 μM HCA increased ROS levels by 5.2-fold compared to DMSO-treated cells. However, downregulation of target proteins PRX1 and PRX2 using shRNAs (short hairpin RNA) significantly reduced HCA-mediated ROS induction (1.6-fold), supporting that PRX1 and PRX2 are targets of HCA for ROS elevation. Additionally, intraperitoneal injection of 50 mg/kg HCA inhibited SW620 tumor growth, resulting in a 59.9 % reduction in tumor volume. CETSA analysis of tumor tissues showed that PRX1 and PRX2 were bound and thus inactivated by HCA in a mouse xenograft model. These findings demonstrate that PRX1 and PRX2 are molecular target proteins responsible for HCA-induced ROS elevation and cancer cell death.